Jealousy and male anxiety: articulations of gender in “the curious impertinent” and the amorous prince - Serrano González, Raquel (The Grove - Working Papers on English Studies, 2016)
The subplot of Aphra Behn’s play The Amorous Prince is a rewriting of “The Impertinent Curious,” an interpolated tale in Don Quixote that depicts a pathologically jealous husband. All-pervasive in both Golden Age Spain and Restoration England, the discourse of jealousy was deployed to explore cultural issues involving identity and power. While contributing to validate the established relations of power, the hegemonic notions of manhood prevailing in each context were contradictory, and hence were subject to subversion and resistance. Sexual jealousy is analysed as a consequence of the paradoxes underlying the culturally specific dominant constructions of gender, which was at the same time an enabling condition of hegemony and a source of male anxiety. My analysis is aimed at determining how this ideological contradiction is managed in each text.